Acute Enhancement of Cardiac Function by Phosphodiesterase Type 1 Inhibition: Translational Study in the Dog and Rabbit. Issue 18 (30th October 2018) - Hashimoto, Toru; Kim, Grace E.; Tunin, Richard S.; Adesiyun, Tolulope; Hsu, Steven; Nakagawa, Ryo; Zhu, Guangshuo; O'Brien, Jennifer J.; Hendrick, Joseph P.; Davis, Robert E.; Yao, Wei; Beard, David; et al.
Abstract : Background: Phosphodiesterase type-1 (PDE1) hydrolyzes cAMP and cGMP and is constitutively expressed in the heart, although cardiac effects from its acute inhibition in vivo are largely unknown. Existing data are limited to rodents expressing mostly the cGMP-favoring PDE1A isoform. Human heart predominantly expresses PDE1C with balanced selectivity for cAMP and cGMP. Here, we determined the acute effects of PDE1 inhibition in PDE1C-expressing mammals, dogs, and rabbits, in normal and failing hearts, and explored its regulatory pathways. Methods: Conscious dogs chronically instrumented for pressure-volume relations were studied before and after tachypacing-induced heart failure (HF). A selective PDE1 inhibitor (ITI-214) was administered orally or intravenously±dobutamine. Pressure-volume analysis in anesthetized rabbits tested the role of β-adrenergic and adenosine receptor signaling on ITI-214 effects. Sarcomere and calcium dynamics were studied in rabbit left ventricular myocytes. Results: In normal and HF dogs, ITI-214 increased load-independent contractility, improved relaxation, and reduced systemic arterial resistance, raising cardiac output without altering systolic blood pressure. Heart rate increased, but less so in HF dogs. ITI-214 effects were additive to β-adrenergic receptor agonism (dobutamine). Dobutamine but not ITI-214 increased plasma cAMP. ITI-214 induced similar cardiovascular effects in rabbits, whereas mice displayed only mild vasodilation and no contractility effects. In rabbits, β-adrenergic receptor blockade (esmolol) prevented ITI-214–mediated chronotropy, but inotropy and vasodilation remained unchanged. By contrast, adenosine A2B -receptor blockade (MRS-1754) suppressed ITI-214 cardiovascular effects. Adding fixed-rate atrial pacing did not alter the findings. ITI-214 alone did not affect sarcomere or whole-cell calcium dynamics, whereas β-adrenergic receptor agonism (isoproterenol) or PDE3 inhibition (cilostamide) increased both. Unlike cilostamide, which further enhanced shortening and peak calcium when combined with isoproterenol, ITI-214 had no impact on these responses. Both PDE1 and PDE3 inhibitors increased shortening and accelerated calcium decay when combined with forskolin, yet only cilostamide increased calcium transients. Conclusions: PDE1 inhibition by ITI-214 in vivo confers acute inotropic, lusitropic, and arterial vasodilatory effects in PDE1C-expressing mammals with and without HF. The effects appear related to cAMP signaling that is different from that provided via β-adrenergic receptors or PDE3 modulation. ITI-214, which has completed phase I trials, may provide a novel therapy for HF. Abstract : Supplemental Digital Content is available in the text.